Cross-validation of three Advanced Clinical Solutions performance validity tests: Examining combinations of measures to maximize classification of invalid performance. Issue 1 (2nd January 2021) - Bain, Kathleen M.; Soble, Jason R.; Webber, Troy A.; Messerly, Johanna M.; Bailey, K. Chase; Kirton, Joshua W.; McCoy, Karin J. M.
Abstract: Use of multiple performance validity tests (PVTs) may best identify invalid performance, though few studies have examined the utility and accuracy of combining PVTs. This study examined the following PVTs in the Advanced Clinical Solutions (ACS) package to determine their utility alone and in concert: Word Choice Test (WCT), Reliable Digit Span (RDS), and Logical Memory Recognition (LMR). Ninety-three veterans participated in clinical neuropsychological evaluations to determine presence of cognitive impairment; 25% of the performances were deemed invalid via criterion PVTs. Classification accuracy of the ACS measures was assessed via receiver operating characteristic curves, while logistic regressions determined utility of combining these PVTs. The WCT demonstrated superior classification accuracy compared to the two embedded measures of the ACS, even in veterans with cognitive impairment. The two embedded measures (even when used in concert) exhibited inadequate classification accuracy. A combined model with all three ACS PVTs similarly demonstrated little benefit of the embedded indicators over the WCT alone. Results suggest the ACS WCT has utility for detecting invalid performance in a clinical sample with likely cognitive impairment, though the embedded ACS measures (RDS and LMR) may have limited incremental utility, particularly in individuals with cognitive impairment.